Effect of laser surface treatment on the some of mechanical properties of AISI 4130 steel - J.M. Taha (Engineering and Technology Journal, 2017)
In this work the surface of an alloy of AISI 4130 steel is hardened by using CW Nd:YAG laser and then study the effect of laser surface hardening on mechanical properties such as yield strength (σy), ultimate tensile strength (σu.T.S), plasticity constant (k),strain hardening coefficient (n) , also evaluate the microstructure and microhardness during the hardening of the alloy. CW Nd:YAG laser was used to scan on the surface of samples by varying the laser beam energies (500,750,1000 mj) with travel speed 500 mm/min of the work table. There are many examinations were done for laser hardened of AISI 4130 steel such as an analysis of microstructure features by using an optical microscopy and microhardness. Also tensile test is carried out for the specimens before and after laser surface treatment. The results of this investigation showed that an improvement in mechanical properties after laser surface hardening, also microhardness decreases faraway the hardened surface toward the center of the specimen. While the microstructure examination showed that the laser energy 1000 mj lead to form fine plate martensite structure more than another energies 500 and 750 mj.